The Influence of Organizational Culture on Turnover through The Quality of Work Life - Saripudin Saripudin; Musa Hubeis; Nancy Yusnita (Journal of Social Science, 2023)
Quality of Work Life (QWL) is an organization's effort to control behavior and maintain the work performance of its employees so that it continues to improve continuously. This study aims to determine the influence of organizational culture, leadership serve and personality on turnover with mediated by the quality of work life. Example 134 respondents. PT Nipindo Primatama Group North Jakarta City. Research Data were analyzed using SEM PLS analysis techniques with the help of SmartPLS program. The results of this study showed that organizational culture, leadership work positive and significant to the quality of work life, the better the organizational culture, leadership serve and personality then the better the quality of employee work life. The results also showed that the leadership serve, personality and quality of working life affect negatively on turnover, while organizational culture directly does not affect on turnover. Quality of employee work life, while a good organizational culture cannot always improve the quality of employee work life, organizational culture can degrade the high quality of employee work life.